Indigenous Law on Land: How Does the Government Build Constitutional Protection Against Indigenous People - Sisca Ferawati Burhanuddin (Jurnal Mantik, 2020)
Indonesia has a lot of cultural diversity and abundant natural resources, one of which is found in the customary law system as one of the traditional laws that has existed for a long time as one of the most influential laws for some Indonesian people. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that basically customary law does not only regulate the community government system, customary law also always plays a role in the ownership of customary land rights, where land rights are starting to experience many disturbances. as well as obstacles in its management and sustainability, to build a customary law that synergizes with state law, customary law begins to adapt and adapt to modern human civilization, basically the Indonesian government has recognized and guaranteed every continuity of the customary law, as contained in the Law and political law in Indonesia.